Developmental Relations between Children's Peer Relationship Quality and Prosocial Behavior: The Mediating Role of Trust. Issue 3 (26th April 2022) - Jambon, Marc; Malti, Tina
Abstract: Positive peer relationships are important for children's prosocial development, yet the mechanisms that explain how peers contribute to prosocial outcomes during the preschool and early school years remain understudied. The present study used a prospective longitudinal design to examine whether children's degree of trust in others mediated the association between prior peer relationship quality and later prosocial behavior in a Canadian sample ( N = 150; T1 M age = 4.53 years, 50% female). Primary caregivers (84% mothers) reported on children's peer relationship quality (at age 4), trust in others (ages 4 and 5), and prosocial behavior (ages 4 and 6). Controlling for initial levels of trust and prosocial behavior at age 4, longitudinal path modeling indicated that higher quality peer relationships directly predicted relative increases in trust at age 5. In turn, increased trust at age 5 predicted relative increases in prosocial behavior at age 6. Consistent with longitudinal mediation, the indirect effect of peer relationship quality on later prosocial behavior via trust was also significant. Sensitivity analyses further indicated that these effects held over and above the potential confounding influence of parental warmth and externalizing behavioral problems (assessed at age 6). Programs designed to promote prosocial skills in early childhood may benefit from an increased emphasis on building and maintaining children's interpersonal trust.